Cell Type-Specific Transcriptional Control of Gsk3β in the Developing Mammalian Neocortex - Nomura, Tadashi; Gotoh, Hitoshi; Kiyonari, Hiroshi; Ono, Katsuhiko (Frontiers in Neuroscience, 2022)
Temporal control of neurogenesis is central for the development and evolution of species-specific brain architectures. The balance between progenitor expansion and neuronal differentiation is tightly coordinated by cell-intrinsic and cell-extrinsic cues. Wnt signaling plays pivotal roles in the proliferation and differentiation of neural progenitors in a temporal manner. However, regulatory mechanisms that adjust intracellular signaling amplitudes according to cell fate progression remain to be elucidated. Here, we report the transcriptional controls of Gsk3β, a critical regulator of Wnt signaling, in the developing mouse neocortex. Gsk3β expression was higher in ventricular neural progenitors, while it gradually declined in differentiated neurons. We identified active cis-regulatory module (CRM) of Gsk3β that responded to cell type-specific transcription factors, such as Sox2, Sox9 and Neurogenin2. Furthermore, we found extensive conservation of the CRM among mammals but not in nonmammalian amniotes. Our data suggest that a mammalian-specific CRM drives the cell type-specific activity of Gsk3β to fine tune Wnt signaling, which contributes to the tight control of neurogenesis during neocortical development.